The evolution of International business 1800-1945. Volume II : British investments and the American mining frontier, 1860-1901 - Spence, Clark C. (London ; New York : Routledge, 2000)
The background of investment. Individual promoters. Co-operative promotion. Promotional methods and techniques. Capitalization problems. Management problems...
Keywords: Economics; Investments; Mineral industries -- West (U.S.) -- Foreign ownership -- History -- 19th century; Corporations, British -- West (U.S.) -- History -- 19th century; Investments, British - West (U.S.) -- History -- 19th century